Effect of Training Mothers Based on Adler-Dreikurs' Approach on Positive and Negative Symptoms of Children with Attention Deficit/Hyperactivity Disorder - Mohsen Amiri (Ravānshināsī-i Afrād-i Istis̠nāyī, 2014)
The purpose of the present study was to investigate effects of training mothers with Adler-Dreikurs approach on decreasing positive and negative symptoms of ADHD in their children and increasing the children’s behavioral performance. The research employed a quasi-experimental method and a pre-and-post design with control group. A total 24 mothers whose children were diagnosed with ADHD were chosen through convenience sampling and were matched into experimental and control groups. The research instruments were the Child Symptom Inventory-4 (CSI-4), the Conners’ Parent Rating Scale, and the Child Behavior Checklist. The training was given to the mothers in the experimental group in ten 90-minute sessions. Both groups completed the questionnaires as the post-test. The data were analyzed using ANCOVA. The results showed effectiveness of the training in increasing the children’s behavioral performance (p < 0.05) and in decreasing symptoms of ADHD and hyperactivity (p < 0.05) but no effect on symptoms of attention deficit. Findings usually suggest that training parents based on Adler-Dreikurs methods decreases children’s behavioral problems and reduces symptoms in children with ADHD.